Exploring the Cunninghamia lanceolata(Lamb.) Hook Genome by BAC Sequencing - Ji, Yuan; Zhu, Liming; Hao, Zhaodong; Su, Shunde; Zheng, Xueyan; Shi, Jisen; Zheng, Renhua; Chen, Jinhui (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: Chinese fir (Cunninghamia lanceolata(Lamb.))Hook is an important economic timber tree in China. However, its genome characteristics have not been extensively assessed. To better understand its genome information, we constructed a Chinese fir bacterial artificial chromosome (BAC) library. A total of 422 BAC clones were selected and divided into 10 pools and sequenced, and with an average insert size of 121 kb, ranging from 97 kb to 145 kb. A total of 61,902,523 bp of reference sequences were sequenced and assembled, and based on an estimated genome size of 11.6 Gb for Chinese fir, the BAC library was estimated to have a total coverage of 0.53% genome equivalents. Bioinformatics analyses were also performed for repeated sequences, tRNAs, coding gene prediction, and functional annotation. The results of this study provide insights into the brief structure of the Chinese fir genome and has generated gene data that will facilitate molecular investigations on the mechanisms underlying tree growth.